1β-Hydroxyalantolactone, a sesquiterpene lactone from Inula japonica, attenuates atopic dermatitis-like skin lesions induced by 2, 4-dinitrochlorobenzene in the mouse. (3rd March 2016) - Lin, Guochao; Gao, Shuang; Cheng, Jinli; Li, Yinghua; Shan, Lei; Hu, Zhenlin
Abstract: Context : 1β-Hydroxyalantolactone (IJ-5) is a sesquiterpene lactone compound isolated from Inula japonica Thunb (Asteraceae). Sesquiterpene lactones have been shown to modulate many processes that influence inflammatory reactions. Objective : The present study examines the protective effect of IJ-5 on atopic dermatitis (AD) in a mouse model induced by 2, 4-dinitrochlorobenzene (DNCB). Materials and methods : AD-like skin lesions were induced in Balb/c mice by sensitizing once with painting 100 μL of 5% DNCB on their shaved back skin and then challenging with 20 μL of 0.2% DNCB five times on their right ears at 3 d interval starting on day 5 post-sensitization. IJ-5 was administrated intraperitoneally at 10 mg/kg 1 h before each DNCB challenge. Results : IJ-5 treatment attenuated DNCB-induced dermatitis severity and right ear swelling. The serum levels of IgE, IL-4, and IL-6 in IJ-5-treated mice were reduced by 54.7, 56.5, and 53.0%, respectively, while the mRNA levels of TNFα, IL-1, IL-4, and IL-6 in back skin lesions of IJ-5-treated mice were reduced by 47.7, 61.5, 57.5, and 58.5%, respectively, compared with untreated controls. Histopathological examination showed that IJ-5 treatment decreased DNCB-induced hypertrophy, hyperkeratosis, and infiltration of inflammatory cells in both ear and back skins. Moreover, IJ-5 suppressed the expression of TNFα, IL-1, and IL-6 with IC50 values of 6.58, 9.48, and 7.01 μM, respectively, and inhibited the activation of NF-κB pathway in TNFα-stimulated HaCat cells. Discussion and conclusion : The present study demonstrates the protective effects of IJ-5 against AD-like skin inflammation and highlights IJ-5 as a potential therapeutic agent for AD.